Evaluation and Enhancement of the Oxygen Reduction Reaction Activity on Hafnium Oxide Nanoparticles Assisted by L(+)-lysine. (20th May 2016) - Chisaka, Mitsuharu; Itagaki, Noriaki
Graphical abstract: Abstract: Evaluation of the oxygen reduction reaction (ORR) on oxide compounds is difficult owing to the insulating nature of oxides. In this study, various amounts of L(+)-lysine were added to the precursor dispersion for the hydrothermal synthesis of hafnium oxide nanoparticles on reduced graphene oxide sheets (HfO x –rGO) to coat the HfO x catalysts with layers of carbon, thereby increasing the conductivity and number of active sites. When the mass ratio of L(+)-lysine to GO, R, was above 26, carbon layers were formed and the amount monotonically increased with increasing R, as noted by cyclic voltammogrametry. X-ray photoelectron spectroscopy and rotating disk electrode analyses revealed that pyrolysis produced ORR-active oxygen defects, whose formation was proposed to involve carbothermal reduction. When 53 ≤  R  ≤ 210, HfO x –rGO contained a similar amount of oxygen defects and ORR activity, as represented by an onset potential of 0.9 V versus the reversible hydrogen electrode in 0.1 mol dm −3 H2 SO4 . However, the number of active sites depended on R due to the amount of L(+)-lysine-derived carbon layers that increased both the number of active sites and resistivity towards oxygen diffusion.